2019
DOI: 10.1038/s42004-019-0214-4
|View full text |Cite
|
Sign up to set email alerts
|

Asphaltene oxide promotes a broad range of synthetic transformations

Abstract: Carbocatalysts, which are catalytically-active materials derived from carbon-rich sources, are attractive alternatives to metal-based analogs. Graphene oxide is a prototypical example and has been successfully employed in a broad range of synthetic transformations. However, its use is accompanied by a number of practical and fundamental drawbacks. For example, graphene oxide undergoes explosive decomposition when subjected to elevated temperatures or microwaves. We found that asphaltene oxide, an oxidized coll… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 38 publications
1
11
0
Order By: Relevance
“…We previously showed that asphaltene-based carbocatalysts feature an advantage over their graphene analogues in that they can be utilized in microwave-assisted chemistry. 17 Building on these results, we focused on employing sAO in microwaveassisted Fischer indole syntheses. Indole derivatives have a Unless otherwise noted, all reactions were performed using 1.2 mmol of phenylhydrazine, 1.0 mmol of cyclohexanone, 2.0 mL of water as solvent and the indicated quantity of catalyst loading at 150 C in a microwave reactor.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We previously showed that asphaltene-based carbocatalysts feature an advantage over their graphene analogues in that they can be utilized in microwave-assisted chemistry. 17 Building on these results, we focused on employing sAO in microwaveassisted Fischer indole syntheses. Indole derivatives have a Unless otherwise noted, all reactions were performed using 1.2 mmol of phenylhydrazine, 1.0 mmol of cyclohexanone, 2.0 mL of water as solvent and the indicated quantity of catalyst loading at 150 C in a microwave reactor.…”
Section: Resultsmentioning
confidence: 99%
“…We recently reported a new carbocatalyst based on asphaltene. 17 While the structure of asphaltene is reminiscent of a graphene sheet, it is relatively small. 18 Subjecting asphaltene to a modied Hummers' method afforded asphaltene oxide (AO), which was found to exhibit catalytic activities similar to that of GO but under a wider range of conditions.…”
Section: Introductionmentioning
confidence: 99%
“…This clear separation increased the solubility and widened the window of redox potential by more than 0.4 V [87]. The redox potentials and solubility of organic redox molecules can be engineered by attaching positively charged and negatively charged functional groups to the aromatic rings [88]. The position of side groups determined the redox potential and solubility in organic redox species [89].…”
Section: Metal-free Redox Electrolytesmentioning
confidence: 99%
“…The scope of the reaction includes aliphatic and aromatic amines, while the latter tolerate both electron withdrawing and electron donating substituents, including halogens, with yields ranging between 17% and 77%. Bielawski and coworkers recently developed a new class of carbocatalysts, asphaltene oxides (AOs) 85 , which are prepared from the asphaltene waste generated during crude oil refining process. Structurally, AO is a truncated analog of GO with lower oxygen content (Scheme 31).…”
Section: Scheme 27 Aerobic Ammoxidation Of Alcohols To Nitriles Promo...mentioning
confidence: 99%